Improvement of Computational Thinking through Interactive Multimedia Learning Based on Initial Mathematical Ability - Angraini, Lilis Marina; Arcat; Sohibun (EDUPEDIA Publisher, 2022)
This study was motivated by the low level of computational thinking (CT) ability in students as witnessed by the author among prospective teachers, along with the changes that came about within the learning system in the move from face-to-face to online learning during the COVID-19 pandemic. This study specifically seeks to improve students’ mathematical computational thinking ability through the use of interactive multimedia-based teaching materials based on initial mathematical ability to support online learning. This quantitative study (quasiexperimental) was conducted at two universities, namely, Universities Islam Riau (UIR) and Universitas Pasir Pengaraian (UPP) in Indonesia. The research subjects were prospective mathematics teachers taking algebraic structure at the UIR (an experimental class) and the prospective mathematics teacher course at the UPP (control class) in the 2021/2022 academic year. The data were collected method through a computational thinking ability test and interview, and the test results data are processed using a statistical test. Normality is assessed using the Kolmogorov–Smirnov test, and homogeneity is assessed using the Levene and two-way analysis of variance (ANOVA) tests. From the two-way ANOVA test, a significance value of 0.001 < 0.05 was obtained. This indicates that an increase is observed in the mathematical computational thinking ability of students who receive learning using interactive multimedia-based teaching material based on initial mathematical ability.